Stellar mass as a galaxy cluster mass proxy: application to the Dark Energy Survey redMaPPer clusters. Issue 4 (21st February 2020) - Palmese, A; Annis, J; Burgad, J; Farahi, A; Soares-Santos, M; Welch, B; da Silva Pereira, M; Lin, H; Bhargava, S; Hollowood, D L; Wilkinson, R; Giles, P; et al.
Abstract: We introduce a galaxy cluster mass observable, μ⋆, based on the stellar masses of cluster members, and we present results for the Dark Energy Survey (DES) Year 1 (Y1) observations. Stellar masses are computed using a Bayesian model averaging method, and are validated for DES data using simulations and COSMOS data. We show that μ⋆ works as a promising mass proxy by comparing our predictions to X-ray measurements. We measure the X-ray temperature–μ⋆ relation for a total of 129 clusters matched between the wide-field DES Y1 redMaPPer catalogue and Chandra and XMM archival observations, spanning the redshift range 0.1 < z < 0.7. For a scaling relation that is linear in logarithmic space, we find a slope of α = 0.488 ± 0.043 and a scatter in the X-ray temperature at fixed μ⋆ of σ _ln T_ X|μ _= 0.266^+0.019_-0.020 for the joint sample. By using the halo mass scaling relations of the X-ray temperature from the Weighing the Giants program, we further derive the μ⋆ -conditioned scatter in mass, finding σ _ln M|μ _= 0.26^+ 0.15_- 0.10 . These results are competitive with well-established cluster mass proxies used for cosmological analyses, showing that μ⋆ can be used as a reliable and physically motivated mass proxy to derive cosmological constraints.